2006
DOI: 10.1016/j.physleta.2005.08.096
|View full text |Cite
|
Sign up to set email alerts
|

Similar impact of topological and dynamic noise on complex patterns

Abstract: Shortcuts in a regular architecture affect the information transport through the system due to the severe decrease in average path length. A fundamental new perspective in terms of pattern formation is the destabilizing effect of topological perturbations by processing distant uncorrelated information, similarly to stochastic noise. We study the functional coincidence of rewiring and noisy communication on patterns of binary cellular automata.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…On the contrary, for chains of regularly connected nodes, a topological perturbation in general leads to a decreasing dynamic complexity. In a previous study [40], we showed this behaviour for synchronous and asynchronous update schemes with different observables. Moreover we showed, that both topological perturbation (i.e., the rewiring of links) and dynamic noise increase the regularizing capacity of an initially undisturbed cellular automaton.…”
Section: Resultssupporting
confidence: 57%
“…On the contrary, for chains of regularly connected nodes, a topological perturbation in general leads to a decreasing dynamic complexity. In a previous study [40], we showed this behaviour for synchronous and asynchronous update schemes with different observables. Moreover we showed, that both topological perturbation (i.e., the rewiring of links) and dynamic noise increase the regularizing capacity of an initially undisturbed cellular automaton.…”
Section: Resultssupporting
confidence: 57%
“…CA have been used in a vast number of investigations to explore the emergence of complex patterns from simple dynamic rules. Originally defined on regular lattices [27], they have also been studied on more complex topologies [15,16,36] and in noisy environments [32,37]. It should be noted that due to the diverse neighborhood sizes (compared to a regular 1D or 2D lattice) and the lack of ordering of neighbors, only a very small set of rules (from classical CA) can be plausibly transferred to general graphs.…”
Section: Cellular Automata On Graphsmentioning
confidence: 99%
“…Both measures have been successfully used for the quantification of pattern complexity in CA-on-graph dynamics (see Section 2.1) [15,16,32,35]. The Shannon entropy E S serves as a measure for the asymmetry between zeros and ones in the time series of each node and, when averaged over all nodes, of the "spatio"-temporal patterns.…”
Section: Entropy Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…On graphs, this classification inevitably fails because of a lacking natural node order. Instead, we apply two entropy-like measures, the Shannon entropy S and the word entropy W , which we have previously shown to provide a feasible framework for the quantification of pattern complexity [10,11,12]. The Shannon entropy S serves as a measure for the homogeneity of the spatio-temporal pattern, by averaging over all nodes: We compare 10 3 random initial conditions on the regular architecture with 10 3 samples of a randomized graph, where the number of incoming and outgoing links of every node is preserved and kept to d = 2, but the link architecture has been randomized [13].…”
mentioning
confidence: 99%